2015
DOI: 10.3892/ol.2015.3206
|View full text |Cite
|
Sign up to set email alerts
|

Proflavin suppresses the growth of human osteosarcoma MG63 cells through apoptosis and autophagy

Abstract: Abstract. Proflavin is one of the novel acridine derivatives that possess various pharmacological effects. Although numerous studies have been performed to investigate proflavin, its effects have not been investigated on the human osteosarcoma MG63 cell line. The core aim of the present study was to test the effects of proflavin on the viability of MG63 cells and the induction of apoptosis and autophagy in MG63 cells. The induction of apoptosis was examined by measuring the changes in the expression of the B-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 29 publications
1
4
1
Order By: Relevance
“…Autophagy and apoptosis are obviously different in terms of morphological or biochemical metabolic pathways, but there is a link between their functions. Due to interaction of apoptosis and autophagyrelated molecules, in some cases, autophagy and apoptosis can promote or antagonize each other [14,15]. Our results suggest that the proliferation rate of HeLa cell in 3-Ma and quercetin group is lower than that in quercetin alone group, indicating that inhibition of autophagy can increase the inhibition rate of HeLa cells.…”
Section: Discussioncontrasting
confidence: 57%
“…Autophagy and apoptosis are obviously different in terms of morphological or biochemical metabolic pathways, but there is a link between their functions. Due to interaction of apoptosis and autophagyrelated molecules, in some cases, autophagy and apoptosis can promote or antagonize each other [14,15]. Our results suggest that the proliferation rate of HeLa cell in 3-Ma and quercetin group is lower than that in quercetin alone group, indicating that inhibition of autophagy can increase the inhibition rate of HeLa cells.…”
Section: Discussioncontrasting
confidence: 57%
“…This finding is consistent with previous studies showing that allicin can induce autophagy in several cell types, such as thyroid cell lines [12] and human liver cancer cells [10]. It has been widely reported that there is a relationship between apoptosis and autophagy which underlies the process of cancer cell death [20,21].…”
Section: Gbm Is One Of the Most Incurable Forms Of Neoplasmssupporting
confidence: 93%
“…It has been demonstrated that autophagy play a protective role against neoplastic disease 48 and deregulation of autophagy is often implicated in several human diseases including cancers. Several studies have shown that tumor cells are defective in autophagy and/or apoptosis pathway.…”
Section: Discussionmentioning
confidence: 99%